Hydrogen bonding rather than cation bridging promotes graphene oxide attachment to lipid membranes in the presence of heavy metals - Li, Huimin; Ji, Haodong; Zhang, Ruijie; Wei Zhang; Pan, Baozhu; Liu, Wen; Sun, Weiling (Environ. Sci.: Nano, 2020)
Interactions between graphene oxide (GO) and cell membranes play a crucial role in the nanotoxicity of GO toward organisms. However, little is known about interactions of GO with lipid membranes in the presence of heavy metals. This study investigated the attachment of GO and adsorption of heavy metals onto simulated cell membranes (spherical supported lipid bilayers, SSLBs) formed by cationic, neutral and anionic lipids, i.e., SSLB(+), SSLB(0) and SSLB(−), using batch experiments, density functional theory (DFT) calculations, and spectroscopic analyses. In the binary systems, the SSLBs bind with GO through hydrogen binding and with heavy metals via complexation. The attachment of GO or adsorption of heavy metals onto SSLBs decreased in the order SSLB(−) > SSLB(0) > SSLB(+), largely controlled by the type and number of functional groups in the SSLBs. Evidence from batch experiments, DFT calculations and spectroscopic analyses confirmed that in the ternary system GO first binds with metals, and then the GO–metal complexes attach to SSLBs via hydrogen bonding through GO rather than cation bridging through metals. Moreover, metal adsorption onto GO strengthens hydrogen bonding by withdrawing electrons from the GO surface. Therefore, in the ternary system, heavy metals promoted the GO attachment to SSLBs. However, GO suppressed the adsorption of heavy metals onto SSLBs by blocking the adsorption sites via steric hindrance. This study highlighted the importance of molecular interactions on assessing the nanotoxicity of GO to cells in the coexistence of heavy metals.